A family of DC-DC converters deduced from impedance source DC-DC converters for high step-up conversion - Liu, Hongchen; Li, Fei; Wheeler, Patrick (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper introduces a family of DC-DC converters based on impedance source DC-DC converters. The derived topology is suitable for high voltage step-up ratios. Compared to the typical impedance source DC-DC converters, the proposed topology dramatically reduces the voltage stresses on the power semiconductor devices. In order to suppress the voltage spikes and recycle the leakage inductance energy, the passive-lossless clamp scheme is designed in this paper. The paper presents an analysis of the converter and results from a prototype converter to validate the topology’s performance.